1995
DOI: 10.1073/pnas.92.13.5969
|View full text |Cite
|
Sign up to set email alerts
|

Positron-emission tomography studies of cross-modality inhibition in selective attentional tasks: closing the "mind's eye".

Abstract: It is a familiar experience that we tend to close our eyes or divert our gaze when concentrating attention on cognitively demanding tasks. We report on the brain activity correlates of directing attention away from potentially competing visual processing and toward processing in another sensory modality. Results are reported from a series of positron-emission tomography studies of the human brain engaged in somatosensory tasks, in both "eyes open" and "eyes closed" conditions. During these tasks, there was a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
98
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(114 citation statements)
references
References 18 publications
14
98
0
Order By: Relevance
“…Prior studies have demonstrated effects of this kind. Using positron emission tomography (PET) to measure changes in regional cerebral blood flow (rCBF) during somatosensory and visual tasks, Kwashima et al [15] observed task-related deactivations in sensory areas involved in processing information directed to the irrelevant or unattended sensory modality. Similarly, in an fMRI study by Laurienti et al [16], auditory stimuli elicited activation in auditory cortex and deactivation in extrastriate visual cortex and vice versa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have demonstrated effects of this kind. Using positron emission tomography (PET) to measure changes in regional cerebral blood flow (rCBF) during somatosensory and visual tasks, Kwashima et al [15] observed task-related deactivations in sensory areas involved in processing information directed to the irrelevant or unattended sensory modality. Similarly, in an fMRI study by Laurienti et al [16], auditory stimuli elicited activation in auditory cortex and deactivation in extrastriate visual cortex and vice versa.…”
Section: Resultsmentioning
confidence: 99%
“…Task-related decreases in BOLD contrast (deactivations) have been reported in fMRI studies [14][15][16][17] and have been correlated with decreased blood oxygenation and neural suppression [17]. Functional neuroimaging studies could therefore provide the desired converging evidence by determining whether a stimulus category, such as faces, evokes spatially discrete BOLD contrast activations and deactivations.…”
Section: Introductionmentioning
confidence: 99%
“…Positron emission tomography (PET) also showed rCBF-decreases in visual (Kawashima, et al 1995) and auditory (Shulman, et al 1997) cortices during spatial-, visual-or selectiveattention tasks, and in auditory and somatosensory cortices during tasks that did not require attention. (Born, et al 2002;Haxby, et al 1994;Shulman, et al 1997) Brain deactivation also has been reported during attention requiring tasks (Deary, et al 2004;Hester, et al 2004;Lawrence, et al 2003); however, whether it reflects neural inhibition of task-irrelevant neural processing or hemodynamic compensatory mechanisms in the brain is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of young adults suggest, however, that the principles of selective processing are similar in other sensory modalities and when shifting attention across sensory modalities (Kawashima et al 1995;Woodruff et al 1996). To investigate whether age-related processing inefficiencies observed in visual attention are similar in auditory attention and when shifting attention across modalities, we conducted an FMRI study with healthy younger and older adults.…”
mentioning
confidence: 99%